Desenvolvimento de videolaringoscópio em manufatura aditiva para utilização em ambiente pré hospitalar - Alves, Marcio Allan de Souza (2024)
While tracheal intubation consists of placing a tube in the trachea for ventilation, laryngoscopy is the procedure for visualizing the larynx by direct or indirect means. Intubation is not always successful and failures to achieve adequate airway patency occur between 0.13 and 6% of cases, compromising ventilation and oxygenation, which can result in serious complications such as broncho aspiration, injuries in the upper airways, cerebral hypoxia, and death. To reduce these failures, video-assisted indirect laryngoscopy or videolaryngoscopy can be used, with some authors recommending it as the first choice in all intubations and not just in cases of difficult airways. What makes implementing this recommendation difficult in developing countries is the high cost of the device. Therefore, the objective of this study was to develop a low-cost video laryngoscope (VL) in additive manufacturing. The VL with a rigid Macintosh-type blade was modeled in the CAD-3D program SolidWorks® and subsequently printed in PLA (polylactic acid). Load and fatigue tests were carried out with the MTS 810/793 testing machine. As main results in terms of ergonomics, the wire attachment was built-in to facilitate gripping and a marker was placed to facilitate camera positioning. Load and fatigue tests showed compliance with the requirements of the ISO 7673:2020 standard. The first requirement determines that when subjected to a traction force of 65 N, the lighting center must not move more than 10 mm (the average movement was only 3.95 mm). Second, when subjected to a traction force of 150 N, the laryngoscope blade should not break (a traction force of up to 348 N was applied and the piece resisted without breaking). Tests were then carried out on mannequins comparing the additive manufacturing videolaryngoscope with the traditional Macintosh-type laryngoscope, intubation rates were 100% successful and all occurred on the first attempt, with an average intubation time of 22.3 seconds and maximizing the distance between the operator’s face and the patient’s airway. It was found that the Macintosh-type PLA videolaryngoscope has the potential to become a low-cost and safe tool in the emergency intubation arsenal.